57 Bystander cardiopulmonary resuscitation and long-term outcomes in out-of-hospital cardiac arrest according to location of arrest. (16th April 2018) - Sondergaard, Kathrine B; Wissenberg, Mads; Gerds, Thomas Alexander; Rajan, Shahzleen; Karlsson, Lena; Kragholm, Kristian; Pape, Marianne; Lippert, Freddy K; Gislason, Gunnar H; Folke, Fredrik; Torp-Pedersen, Christian; Hansen, Steen Moller
Abstract : Aim: Bystander cardiopulmonary resuscitation (CPR) has increased in several countries following nationwide initiatives to facilitate bystander resuscitative efforts in out-of-hospital cardiac arrest (OHCA). We examined the importance of public or residential location of arrest on temporal changes in bystander CPR and outcomes. Method: From the nationwide Danish Cardiac Arrest Registry, all OHCAs from 2001–2014 of presumed cardiac cause and between 18–100 years of age were identified. Arrests witnessed by emergency medical services personnel were excluded. Results: Of 25, 505 OHCAs, 26.4% (n=6, 738) and 73.6% (n=18, 767) were in public and residential locations, respectively. Bystander CPR increased during 2001–2014 in both locations: from 36.4% (95% confidence interval [CI] 30.6% to 42.6%) to 83.1% (95% CI: 80.0% to 85.8%) in public (p<0.001) and from 16.0% (95% CI: 13.2% to 19.3%) to 61.0% (95% CI: 58.7% to 63.2%) in residential locations (p<0.001). Concurrently, 30 day survival increased in public from 6.4% (95% CI: 4.0% to 10.0%) to 25.2% (95% CI: 22.1% to 28.7%) (p<0.001), and in residential from 2.9% (95% CI: 1.8% to 4.5%) to 10.0% (95% CI: 8.7% to 11.4%) (p<0.001). Among 2, 281 30 day survivors, one-year risk of anoxic brain damage/nursing home admission during 2001–2014 decreased from 18.8% (95% CI: 6.6% to 43.0%) to 6.8% (95% CI: 3.9% to 11.8%) in public (p<0.001), whereas the corresponding change was insignificant in residential locations from 11.8% (95% CI: 3.3% to 34.3) to 17.6% (95% CI: 12.7% to 23.9%) (p=0.52). Conclusion: During 2001–2014, bystander CPR and 30 day survival more than doubled in both public and residential OHCA locations. A significant decrease in anoxic brain damage/nursing home admission was observed among 30 day survivors in public, but not among survivors from residential OHCAs. Conflict of interest: None Funding: Trygfonden Foundation KB Sondergaard.